Respuesta :
If the reaction is
X + Y → Products
Then the rate is
R = k[X]ᵃ [Y]ᵇ
Where,
R = the rate of the reaction (mol L⁻¹ s⁻¹)
k = rate constant
[X] and [Y] = concentrations of the reactants (mol L⁻¹)
a = order of the reaction with respect to X
b = order of the reaction with respect to Y
overall reaction order, n = a + b
according to the given rate expression,
rate = [a][b]³
order of the reaction with respect to 'a' is 1
order of the reaction with respect to 'b' is 3
Overall reaction order = 1 + 3
= 4
X + Y → Products
Then the rate is
R = k[X]ᵃ [Y]ᵇ
Where,
R = the rate of the reaction (mol L⁻¹ s⁻¹)
k = rate constant
[X] and [Y] = concentrations of the reactants (mol L⁻¹)
a = order of the reaction with respect to X
b = order of the reaction with respect to Y
overall reaction order, n = a + b
according to the given rate expression,
rate = [a][b]³
order of the reaction with respect to 'a' is 1
order of the reaction with respect to 'b' is 3
Overall reaction order = 1 + 3
= 4
The order of reaction in a is 1 while the order of reaction in b is 3.
What is order of reaction?
The rate law is obtained from the reaction equation or from experiment. We can determine the order of reaction by summing up the exponents in the rate law as shown in the equation of the rate law.
Now, we have; rate = k[a][b]3, the order of reaction in a is 1 while the order of reaction in b is 3.
Learn more about order of reaction: https://brainly.com/question/15365313